Reported Barriers to Mental Health Care in Three Samples of U.S. Army National Guard Soldiers at Three Time Points. Issue 4 (26th August 2014) - Valenstein, Marcia; Gorman, Lisa; Blow, Adrian J.; Ganoczy, Dara; Walters, Heather; Kees, Michelle; Pfeiffer, Paul N.; Kim, H. Myra; Lagrou, Robert; Wadsworth, Shelley MacDermid; Rauch, Sheila A. M.; Dalack, Gregory W.
Abstract: The military community and its partners have made vigorous efforts to address treatment barriers and increase appropriate mental health services use among returning National Guard soldiers. We assessed whether there were differences in reports of treatment barriers in 3 categories (stigma, logistics, or negative beliefs about treatment) in sequential cross‐sectional samples of U.S. soldiers from a Midwestern Army National Guard Organization who were returning from overseas deployments. Data were collected during 3 time periods: September 2007–August 2008 ( n = 333), March 2009–March 2010 ( n = 884), and August 2011–August 2012 ( n = 737). In analyses using discretized time periods and in trend analyses, the percentages of soldiers endorsing negative beliefs about treatment declined significantly across the 3 sequential samples (19.1%, 13.9%, and 11.1%). The percentages endorsing stigma barriers (37.8%, 35.2%, 31.8%) decreased significantly only in trend analyses. Within the stigma category, endorsement of individual barriers regarding negative reactions to a soldier seeking treatment declined, but barriers related to concerns about career advancement did not. Negative treatment beliefs were associated with reduced services use ( OR = 0.57; 95% CI [0.33, 0.97]).